2016
DOI: 10.1080/15017419.2016.1222306
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the individual placement and support approach – facilitators and barriers

Abstract: The individual placement and support approach (IPS) has become a widely recognized evidence-based practice to provide work for more people with severe mental illness. The aim of this literature review was to identify and evaluate research on implementation of IPS, focusing on facilitators and barriers. Contextual, local organizational, cooperation/team and individual factors influence the implementation process. Key facilitators are the use of a fidelity scale to measure and develop quality and the employment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 29 publications
3
71
0
4
Order By: Relevance
“…Trotz guter Evidenz und Verankerung in den Behandlungsleitlinien werden wirksame Interventionen zur Förderung arbeitsbezogener Teilhabe gegenwärtig zu selten während der klinischen Behandlung eingesetzt. Dieser Missstand ist folgenschwer, weil durch solche Interventionen der Exklusion aus dem Arbeitsleben und der damit einhergehenden Verschlechterung der Funktionalität frühzeitig entgegengewirkt werden könnte [8,9]. Insbesondere Schnittstellenprobleme und Versorgungslücken zwischen klinischer Versorgung (SGB V), Rehabilitation (SGB II, III, IX) und Eingliederungshilfe (SGB XII) sowie die fehlende Zusammenarbeit mit den Betrieben und Arbeitgebern erschweren diesen Prozess [10,11].…”
Section: Introductionunclassified
“…Trotz guter Evidenz und Verankerung in den Behandlungsleitlinien werden wirksame Interventionen zur Förderung arbeitsbezogener Teilhabe gegenwärtig zu selten während der klinischen Behandlung eingesetzt. Dieser Missstand ist folgenschwer, weil durch solche Interventionen der Exklusion aus dem Arbeitsleben und der damit einhergehenden Verschlechterung der Funktionalität frühzeitig entgegengewirkt werden könnte [8,9]. Insbesondere Schnittstellenprobleme und Versorgungslücken zwischen klinischer Versorgung (SGB V), Rehabilitation (SGB II, III, IX) und Eingliederungshilfe (SGB XII) sowie die fehlende Zusammenarbeit mit den Betrieben und Arbeitgebern erschweren diesen Prozess [10,11].…”
Section: Introductionunclassified
“…I tillegg legger individuelle faktorer som utfordringene til den enkelte bruker og veiledernes egen profesjonsstandard føringer for oppfølgingen. En rekke studier har vist hvordan disse faktorene som utgjør rammebetingelsene for arbeidet til hjelpeapparatet, også kan utgjøre barrierer som hindrer personer med psykiske helseproblemer å motta det fagfeltet konkluderer med er den beste oppfølgingen (se Bonfils, Hansen, Dalum & Eplov 2016;Bond, Becker, Drake, Rapp, Meisler, Lehman, Bell & Blyler 2001;Proctor, Landsverk, Aarons, Chambers, Glisson & Mittman 2009). Overordnede prioriteringer og retningslinjer kan vaere motstridende.…”
Section: Barrierer Dilemmaer Og Mestringsstrategierunclassified
“…However, structured process evaluations of IPS are scarce. A recent review on implementation studies of supported employment revealed that the investigation of implementation issues take widely different approaches, from re ections based on anecdotes to semi-structured interviews and surveys [21]. The lack of common approaches makes it di cult to get an overview of implementation challenges that are generic across contexts, or speci c to certain contexts.…”
Section: Introductionmentioning
confidence: 99%